Psychosocial Treatment Interventions for People with Severe Mental Illness in a Community - Östman, Margareta (International Journal of Psychosocial Rehabilitation, 2015)
We surveyed 80 people with severe mental illness living in the community in Malmö, Sweden in order to determine their views on the psychosocial interventions many had received from psychiatric services. No measurable differences in back- ground aspects, including self-stated diagnosis and quality of life, were found between those who received interventions and those who did not. However, younger people were more often given cognitive behavior therapy, while individuals liv- ing in their own apartments tended to be the recipients of cognitive behavior therapy, assertive community treatment pro- grams, and family interventions. Out findings showed that psychiatric services not only select people with a high quality of life for psychosocial interventions, but our results indicate that such interventions are generally directed toward people whose severe mental illness lies outside the spectrum schizophrenia disorders.